Implementasi Media Roda Berputar untuk Meningkatkan Hasil Belajar Peluang Kelas VI UPT SDN Kutorejo 1 - Nindi Riska Nur Faidah; Natasya Khofifah Firdaus; Niken Dwi Juliyanti; Sukisno Sukisno; Dwi Retmawati (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This study aims to improve mathematics learning outcomes on probability material through the application of rotating wheel media in class 6A UPT SDN Kutorejo 1. Probability material is considered difficult by students because it is abstract and requires logical thinking skills. This study uses the PTK method with two cycles involving 29 students. Each cycle consists of planning, action, observation, and reflection. The rotating wheel media used is in the form of a circle that can be rotated and contains pictures of typical Tuban souvenirs as objects of probability that students must calculate in groups and independently. The results of the study showed a significant increase in student learning outcomes, marked by an increase in the average score from pretest to posttest in each cycle. In addition, the rotating wheel media also increased student learning motivation and active involvement in learning. PjBL approach combined with this media makes learning more interactive, and fun. In conclusion, the use of rotating wheel media is effective in helping students understand the concept of probability, improving learning outcomes, and overcoming abstract mathematics learning difficulties. The recommendation of this study is the use of rotating wheel media as an alternative innovation in mathematics learning in elementary schools.